1996
DOI: 10.1002/anie.199615521
|View full text |Cite
|
Sign up to set email alerts
|

The [Mn(μ‐O)(μ‐PhBO2)2]2+ Unit: A New Structural Model for Manganese‐Containing Metalloproteins

Abstract: By employing boronato instead of carboxylato bridges in the dication [Mn 2IV(μ‐O)‐(μ‐PhBO2)2L2]2+ (L = 1,4,7‐trimethyl‐1,4,7‐triazacyclononane), a Mn 2IV unit has been stabilized for the first time. Together with the di‐μ‐carboxylato‐μ‐oxodimanganese complexes of analogous structure, there is now an “isostructural series” available containing Mn 2II, MnIIMnIII, Mn 2III, MnIIIMnIV, Mn 2IV units. The Mn K‐edge energy of the corresponding complexes increases linearly with increasing oxidation level. This is of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 20 publications
5
68
0
Order By: Relevance
“…The molecular structure of 4 is presented in Fig. 3 (3.193(1) Å ) [34]. Interestingly, all complexes show intermolecular interactions with solvent molecules or anions, owing to the presence of an N-H moiety within the ligand L-Me 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure of 4 is presented in Fig. 3 (3.193(1) Å ) [34]. Interestingly, all complexes show intermolecular interactions with solvent molecules or anions, owing to the presence of an N-H moiety within the ligand L-Me 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to 4, the structure of this complex was proposed on the basis of the mass spectrum (field desorption) of its solution in CH 2 Cl 2 which showed only a strong signal attributable to [Ni 2 (µ-Cl) 3 …”
Section: Resultsmentioning
confidence: 99%
“…In principle, an alternative structure is [Ni 2 Cl 2 (µ-Cl) 2 (L) 2 ] and this would be composed from a pair of edge-sharing octahedra. However, previous studies [29] have indicated that for dinuclear metal halide adducts of 1,4,7-trimethyl-1,4,7-triazacyclononane, structures containing edge-sharing octahedra exhibit unfavourable steric interactions so that structures containing face-sharing octahedra (as in [Ni 2 (µ-Cl) 3 (Lx) 2 ]Cl) are formed in preference. Regardless of the metal used, TACN ligands bestow a defined shape on the resultant complexes since these ligands always coordinate in a facial manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations